2016
DOI: 10.4088/jcp.15m10239
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind, Randomized, Controlled Pilot Trial of <em>N</em>-Acetylcysteine in Veterans With Posttraumatic Stress Disorder and Substance Use Disorders

Abstract: Objective The antioxidant N-Acetylcysteine (NAC) is being increasingly investigated as a therapeutic agent in the treatment of substance use disorders. Preclinical and clinical findings suggest that NAC normalizes extracellular glutamate by restoring the activity of glutamate transporters and antiporters in the nucleus accumbens. This study explored the efficacy of NAC in the treatment of post-traumatic stress disorder (PTSD), which frequently co-occurs with substance use disorders (SUD) and shares impaired pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 42 publications
(36 reference statements)
1
63
0
Order By: Relevance
“…This effect persisted for 4 weeks after stopping NAC. Subjects also reported improvements in CAPS scores of PTSD symptoms and CAPS intrusive thoughts score …”
Section: Drug Cue–induced Neuroplasticitymentioning
confidence: 93%
“…This effect persisted for 4 weeks after stopping NAC. Subjects also reported improvements in CAPS scores of PTSD symptoms and CAPS intrusive thoughts score …”
Section: Drug Cue–induced Neuroplasticitymentioning
confidence: 93%
“…Another clinical trial assessed the effects N-acetylcysteine (vs placebo) in combination with cognitive-behavioral therapy on post-traumatic stress disorder symptomology and substance abuse (i.e., alcohol use disorder or cocaine use disorder) among 35 dual-diagnosed veterans (Back et al, 2016). The investigators found that active N-acetylcysteine maintenance (2,400 mg/day for eight weeks) significantly reduced drug craving and depression, although no medication effects on drug-taking behavior were found.…”
Section: Drugs Of Abuse and Glial Cell Activitymentioning
confidence: 99%
“…Likewise, a chronic unpredictable stress rat model of depression markedly downregulates EAAT2 and EAAT3 in the hippocampus ( Zhu et al, 2017 ). Also, acute stress in rats causes an enduring reduction of GLT-1 in the NAc ( Garcia-Keller et al, 2016 ), and a recent double-blind clinical trial in veterans comorbid for posttraumatic stress disorder and substance use disorder revealed that NAC reduced both drug craving and symptoms of posttraumatic stress disorder ( Back et al, 2016 ). Sub-anesthetic ketamine, an off-label treatment for refractory depression increasingly used in the clinic, rescued this deficit and the associated behavior ( Zhu et al, 2017 ).…”
Section: Perspectivesmentioning
confidence: 99%